Community Empowerment Strategy In Muntigunung Village, Indonesia - Mutria Farhaeni; Elsita Lisnawati Guntar; Martini, Sri (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
This article examines community empowerment strategies in Muntigunung village, which is the poorest village in Bali. To alleviate the basic problems faced by local communities, the Muntigunung Environmental Development Program was developed with a special focus on the air, economic, health and education sectors. With the aim of improving the economy and creating productive jobs, products were developed from natural resources that already exist in Muntigunung, such as cashew nuts and palm sugar. This was then continued with the development of new products made from rosella, mango and moringa. The aim of this research is to determine the empirical problems that occur. The author emphasizes the role of the Company in empowering the community in Muntigunung village in terms of the forms and obstacles in carrying out its activities. The method in this research is a qualitative method to produce descriptive data, both in the form of written and verbal expressions from people and observed behavior. The author also intends to understand the meaning contained so that he can find the essence conveyed in this empowerment. It is hoped that this essence can find sources of prosperity contained in the community empowerment strategy in improving welfare in Muntigunung Village. The community empowerment strategy in Muntigunung Village has brought significant changes in various aspects of community life. Economic development, improving education and health, infrastructure development, as well as women's empowerment and environmental conservation are some of the areas that have experienced improvement. This success shows that with the right approach, community empowerment can create sustainable change and improve the overall quality of life.